Copper and Gold Cyclic (Alkyl)(amino)carbene Complexes with Sub‐Microsecond Photoemissions: Structure and Substituent Effects on Redox and Luminescent Properties. Issue 19 (24th March 2017) - Romanov, Alexander S.; Becker, Ciaran R.; James, Charlotte E.; Di, Dawei; Credgington, Dan; Linnolahti, Mikko; Bochmann, Manfred
Abstract: Copper and gold halide and pseudo‐halide complexes stabilised by methyl‐, ethyl‐ and adamantyl‐substituted cyclic (alkyl)(amino)carbene (CAAC) ligands are mostly linear monomers in the solid state, without aurophilic Au⋅⋅⋅Au interactions. ( Et2 L)CuCl shows the highest photoluminescence quantum yield (PLQY) in the series, 70 %. The photoemissions of Me2 L and Et2 L copper halide complexes show S1 →S0 fluorescence on the ns time scale, in agreement with theory, as well as a long‐lived emission. Monomeric ( Me2 L)CuNCS is a white emitter, whereas dimeric [( Et2 L)Cu(μ‐NCS)]2 shows intense yellow emission with a photoluminescence (PL) quantum yield of 49 %. The reaction of ( Ad L)MCl (M=Cu or Au) with phenols ArOH (Ar=Ph, 2, 6‐F2 C6 H3, 2, 6‐Me2 C6 H3, 3, 5‐ t Bu2 C6 H3, 2‐ t Bu‐5‐MeC6 H3, 2‐pyridyl), thiophenol, or aromatic amines H2 NAr′′ (Ar′=Ph, 3, 5‐(CF3 )2 C6 H3, C6 F5, 2‐py) afforded the corresponding phenolato, thiophenolato and amido complexes. Although the emission wavelengths are only marginally affected by the ring substitution pattern, the PL intensities respond sensitively to the presence of substituents in the ortho or meta positions. In gold aryloxides, PL is controlled by steric factors, with strong luminescence in compounds with Au‐ O ‐C‐C torsion angles <50°. Calculations confirm the dependence of oscillator strength on the torsion angle, as well as the inter‐ligand charge transfer nature of the emission. The HOMO/LUMO energy levels were estimated based on first reduction and oxidation potentials. Abstract : CAAC shining bright : Copper and gold complexes stabilised by cyclic (alkyl)(amino)carbene ligands ( R L)MX, in which X=halide, pseudo‐halide, amide, or aryloxide, represent a large class of photoluminescent materials, with emission lifetimes ranging from nanosecond to microsecond regimes.